Dissolved and particulate phosphorus concentration and export patterns in headwater streams draining Boreal Plain watersheds one year after experimental forest harvest and postharvest silvicultural activities. (1st August 2008) - Burke, J M; Putz, G; Smith, Daniel W; Prepas, E E
Abstract : This study examined total dissolved (TDP) and particulate phosphorus (PP) concentration and export in nine headwater streams draining Boreal Plain forests in Alberta, Canada, during the growing season and autumn before and in the first year after winter harvest in four of the watersheds. Mechanical and chemical site preparation was also conducted before and during the post-harvest sampling period. During the growing season, TDP and PP concentrations in streams draining harvested watersheds were higher than in the reference streams at storm peaks ( P ≤ 0.08) and along the falling limbs of storm flows ( P ≤ 0.03). We postulate that forestry activities enhanced TDP leaching from watershed soils after they became saturated. This promoted the growth of periphyton in streams, which subsequently sloughed off during high flows. In autumn, TDP concentrations were higher in streams draining harvested watersheds along the rising limb, at the storm peaks, and along the falling limbs ( P ≤ 0.05). However, PP concentrations in autumn were similar in harvested and reference streams along the rising limb ( P = 0.19) and were lower in harvested streams at the storm peaks and along the falling limbs ( P ≤ 0.08). No differences in TDP or PP concentration were detected between harvested and reference streams during baseflow-dominated periods. Mean TDP and PP export coefficients tended to be higher in the post-harvest than pre-harvest year in both reference and harvested watersheds. After normalization to precipitation inputs, this change ("impact ratio") was 153% and 130% higher in harvested than reference watersheds for TDP and PP, respectively ( P ≤ 0.08). The TDP impact ratio and percent of the watershed area cut were positively related ( r 2 = 0.95, P = 0.02). A 30 m riparian buffer strip in two harvested watersheds did not appear to reduce the harvest response.